Critical Synthesis Package: Neurology Clerkship Objective Structured Clinical Examination - Andrea Leep Hunderfund (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Neurology Clerkship OSCE; and (2) a copy of the Neurology Clerkship OSCE instrument and case files developed by Angela Blood, MPH, MBA. The Neurology Clerkship OSCE is designed to assess the clinical skills of medical students at the end of a required 4-week neurology clerkship utilizing two 30-minute standardized patient (SP) encounters (selected from among four available cases) depicting common neurologic presentations. The score for each encounter is based on three checklists: two completed by the SP for expected elements related to history taking and the neurologic examination, and one completed by a faculty rater for expected elements in a post-encounter written formulation. Scores from each encounter are then averaged to derive an overall OSCE score. The Neurology Clerkship OSCE generates reliable assessments of medical student clinical performance that correlates with increasing clinical experience (based on clerkship order), better National Board of Medical Examiners standardized examination scores, and better categorical ratings by faculty on standard written assessment forms. Studies describe its use primarily for summative purposes (i.e., to determine clerkship grades), but the Neurology Clerkship OSCE could also be used for formative feedback or program evaluation. Studies designed to assess the reliability of the Neurology Clerkship OSCE for high-stakes assessments (e.g., using generalizability analysis) and that provide additional consequential validity evidence are needed. Studies are also needed to evaluate performance characteristics of the Neurology Clerkship OSCE among learners at different stages of training, from different health professions, in different settings, and at different time points during the academic year.